Radiographic and Venographic Appearance of Healthy and Laminitic Feet in Amiata Donkeys - Nocera, Irene; Aliboni, Benedetta; Ben David, Liri; Gracia-Calvo, Luis Alfonso; Sgorbini, Micaela; Citi, Simonetta (Frontiers in Veterinary Science, 2020)
Introduction: Laminitis is a debilitating disorder resulting in irreversible anatomical changes in the feet of equids. Assessing specific anatomical features through radiography and venography provides diagnostic and prognostic information. The reference ranges are well-established in horses, but not in donkeys. It is also uncertain as to whether these ranges can be applied to every donkey breed. The present study characterizes the radiological and venographic hoof anatomy of healthy feet of Amiata donkeys and defines the changes associated with severe and mild laminitis. Materials and Methods: A total of 16 forefeet were evaluated in 8 Amiata jennies. The animals underwent musculoskeletal examination, Obel grading assessment and radiological evaluation. Based on clinical examination and radiographic findings, the forefeet were grouped as healthy, mild or severe laminitic feet, thus the digital venograms were performed according to the group definition. Results: Radiology revealed 7/16 healthy, 4/16 mild laminitic, and 5/16 severe laminitic forefeet. Statistical analysis showed differences between the healthy and laminitic forefeet for the dorsal angle (p < 0.0001) and angle of solar aspect (p < 0.0001) of the distal phalanx, for deviation between dorsal aspect of distal phalanx and the hoof wall (p < 0.0001) and phalangeal rotation angle (p = 0.0032). Venography was abnormal in mild and severe laminitic forefeet. In particular, the vascularization was reduced or absent at the lamellar-circumflex junction dorsally, at the sub-lamellar vascular bed and at the circumflex veins. Coronary plexus vascularization was absent in severe laminitic forefeet. Discussion and Conclusions: This study provides the radiological parameters for the assessment of healthy and laminitic forefeet of Amiata donkeys. The mild laminitic foot venogram showed decreased vascularization mainly on lamellar-circumflex junction and sub-lamellar vascular bed, in latero-medial views. The severe laminitic foot showed very poor or absent vascularization in multiple areas. The technique is easily applicable and provides diagnostic support in laminitis.